An experimental comparison of evaporation and condensation heat transfer coefficients for HFC-134a and CFC-12 - Eckels, Steven J.; Pate, M.B. (My University, 1991)
Experimental heat transfer coefficients are reported for HFC-134a and CFC-12 during in-tube single-phase flow, evaporation and condensation. These heat transfer coefficients were measured in a horizontal, smooth tube with an inner diameter of 8.0 mm and a length of 3.67 m. The refrigerant in the test-tube was heated or cooled by using water flowing through an annulus surrounding the tube. Evaporation tests were performed for a refrigerant temperature range of 5–15°C with inlet and exit qualities of 10 and 90%, respectively. For condensation tests, the refrigerant temperature ranged from 30 to 50°C, with et and exit qualities of 90 and 10%, respectively. The mass flux was varied from 125 to 400 kg m−2 s−1 for all tests. For similar mass fluxes, the evaporation and condensation heat transfer coefficients for HFC-134a were significantly higher than those of CFC-12. Specifically, HFC-134a showed a 35–45% increase over CFC-12 for evaporation and a 25–35% increase over CFC-12 for condensation. Résumé On rapporte les coefficients de transfert de chaleur expérimentaux, pour le HFC-134a et le CFC-12, au cours d'un écoulement monophasique, à l'intérieur d'un double tube, et au cours de l'évaporation et de la condensation. Ces coefficients de transfert de chaleur ont été mesurés dans un tube lisse horizontal d'un diamètre intérieur de 8 mm et d'une longueur de 3,67 m. Le frigorigène dans le tube d'essai était chauffé ou refroidi par circulation d'eau dans un espace annulaire entourant le tube. Pour l'évaporation, les essais ont été effectués dans une plage de températures du frigorigène comprises entre 5 et 15°C, avec des qualités d'entrée et de sortie de 10 et 90% respectivement. Pour les essais de condensation, les températures du frigorigène étaient comprises entre 30 et 50°C, avec des qualités d'entrée et de sortie de 90 et 10% respectivement. Le flux massique a varié de 125 à 400 kg m−2 s−1 pour tous les essais. Pour des flux massiques similaires, les coefficients de transfert de chaleur d'évaporation et de condensation, pour le HFC-134a, étaient nettement supérieurs à ceux du CFC-12. Plus précisément, le coefficient de transfert de chaleur à l'évaporation du HFC-134a était de 35 à 45% supérieur à celui du CFC-12, et le coefficient de transfert de chaleur à la condensation supérieur de 25 à 35%.
Citation: Eckels, S.J. and M.B. Pate, An experimental comparison of evaporation and condensation heat transfer coefficients for HFC-134a and CFC-12.International Journal of Refrigeration, 1991. 14(2): p. 70-77.
Keywords: Alternative Refrigerants; Cfc-12; Coefficients De Transfert De Chaleur Expérimentaux; Experimental Heat Transfer Coefficients; Frigorigènes De Substitution; Hfc-134A